Diagnostic test of Rapid antigen SARS Cov-2 against RT-PCR on suspected symptomatic COVID-19 patients at Rato Ebu Hospital Bangkalan - Anik Handayati; Edy Haryanto (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
COVID-19 is caused by the SARS-CoV-2 virus. Two tests to detect the SARS-CoV-2 virus are the rapid antigen test and RT-PCR. The gold standard for testing for COVID-19 is RT-PCR. The high number of Covid-19 sufferers in Madura plus the RT-PCR examination takes a long time. Rapid antigen examination is one of the Covid-19 screening solutions that should be tested because it offers fast examination times. This study aims to determine the sensitivity and specificity of the SARS COV-2 rapid antigen test to RT PCR for the diagnosis of COVID 19. This type of research is an analytical study with a cross-sectional design. The study was conducted at Rato Ebu Hospital Bangkalan from July-September 2021. The sample of this study was suspected symptomatic COVID-19 patients who were examined using the SARS-CoV-2 rapid antigen and RT-PCR using purposive sampling of as many as 60 people. Diagnostic test method by measuring the sensitivity and specificity of rapid antigen to RT-PCR. Based on the results of the study, it can be concluded that the sensitivity of the SARS Cov-2 Rapid Antigen to RT-PCR is 82.97% and the specificity of the SARS Cov-2 Rapid Antigen to RT-PCR is 100%.